Acesso à justiça, mediação familiar e eficiência : uma análise das varas de família de São Luís /MA - Aires, Naiane de Araujo Garcez (2022)
This study is aimed to understand the scenario of access to justice and family mediation in literature and legislation; analyzed the institute of efficiency as a fundamental right and its indicators in civil proceedings; understood which indicators can be used to measure the success of mediation attempts; carried out a quantitative-qualitative data survey that allowed us to investigate the presence of efficiency indicators in consensual circles in Sao Luís, Maranhão. Documental and bibliographic analysis was used to achieve the purposes of the study, with procedures of systematic literature review on the themes of access to justice, family mediation and efficiency, as well as field research through data collection to ascertain the number total number of family actions pending in the family courts of São Luís/MA in the period from 2018 to 2022. As the result of the research, it was confirmed the hypothesis that it is possible to affirm the efficiency of self-composition in such actions as a way of viability of access to justice based on the analysis of quantitative-qualitative data offered by the Judiciary bodies in relation to the reality of family courts in São Luís/MA.